Gendered institutions in plant genetic resources management Negotiating rules of collective action in Kerala, India - Martina Aruna Padmanabhan (International Research Workshop on `Gender and Collective Action' 17-21 October 2005, Chiang Mai, Thailand, 2005)
Collective action aims at the joint management of common pool resources. Agrobiodiversity at community level is conceptualized as a collective resource, requiring the management of single varieties and their interrelations within an farming-system. In the rice dominated agriculture in the uplands of Kerala, India, few community groups continue maintaining and thus conserving their high diversity in landraces. Faced with the challenges of devastating prices for rice, their traditional system of collective action to exchange seed material and knowledge is endangered. A new institutional mechanisms to manage biodiversity is the People's Biodiversity Register, a mandatory documentation procedure to enable cost and benefit sharing under the Convention on Biological Diversity. The comparative analysis of these contrasting cases of an indigenous and an administered effort is concerned with the importance of the category gender for the rules structuring the actions of the groups. Gender is perceived as an institution, constructing regulations of access and conduct for its members, shaping the room of maneuver. Do the core elements constituting collective action, namely reputation, trust and reciprocity (Ostrom 2005a) imply different consequences for men and women? Do the rules structuring group mobilization imply other consequences for men and men in the same given context and regarding the management of the same resource? Where do we observe differences and to which effect? Since action resources are very much determined by the existing construction of gender, the questions is how collective action enlarges or inhibits the repertoire of men and women. Based on 2005 empirical data, the paper will analyze the tribal community of Kuruichias and the people's Biodiversity Register with special emphasis on the analytical category of gender concerning the core elements trust, reciprocity and reputation of collective action